Phytochemical Screening and Antioxidant Activity Testing of Young and Old Bidara Fruit Using the 2,2-Diphenyl-1-picrylhydrazyl (DPPH) Method - Pratiwi, Lidia Wahyu Pratiwi; Jayanti, Gatra Ervi Jayanti; Faisal, Faisal; Wulandari, Dian Novita Wulandari; Widyaningrum, Ike Widyaningrum (JSMARTech, 2026)
This study evaluated the phytochemical constituents and antioxidant activity of Ziziphus mauritiana fruit at young and old ripening stages. Ethanol extracts were subjected to qualitative phytochemical screening and antioxidant activity assessment using the DPPH assay. Both young and old fruit extracts tested positive for alkaloids but lacked detectable flavonoids, tannins, saponins, and triterpenoids. Antioxidant activity was weak in both extracts, with IC₅₀ values of 3882.44 ppm (young) and 4391.79 ppm (old). Statistical analysis showed no significant difference in antioxidant activity between ripening stages (p > 0.05). Young fruit displayed slightly higher inhibition at increasing concentrations. These results suggest that the ripening stage does not significantly affect antioxidant activity in Z. mauritiana fruit. Further research with alternative extraction methods and assays is recommended.